Non-Langerhans cell histiocytosis in a child with Kawasaki disease - Kuo, Ho-Chang (BMJ Publishing Group, 2009)
Polymorphous skin rashes are one of the major presentations in children with Kawasaki disease. This report describes an unusual presentation of a skin rash (non-Langerhans cell histiocytosis) in a 4-month-old baby with resistance to intravenous immunoglobulin (IVIG) treatment and coronary artery dilatation. Though refractory to repeat dosages of IVIG treatment, the patient had a favourable response to methylprednisolone pulse therapy.